ABC's of Leadership uncommon leaders from the bottom up - McGowan, Effua (Effua McGowan, 2020)
When leaders come to their true senses, there is only one thing left to do. Keep going in a way that helps the whole team. This book shows you how to be a leader that stands out, makes a real difference and how people perceive leaders who make a difference in their lives for the better.
Keywords: Leadership